Investigation of the computational burden effects of self-tuning fuzzy logic speed controller of induction motor drives with different rules sizes - Yahya Farah, Nabil Salem; Talib, Md Hairul Nizam; Ibrahim, Zulkifilie; Azri, Maaspaliza; Mat Lazi, Jurifa; Abdullah, Qazwan; Aydoğdu, Ömer; Mat Isa, Zainuddin (Institute of Electrical and Electronics Engineers Inc., 2021)
Fuzzy Logic Controller (FLC) as speed controller is preferred in many AC machine drives, due to its ability to handle model non-linearity, speed variations and parameters change. Additionally, Self-Tuning FLC (ST-FLC) is a modified FLC controller to overcome the issues associated with a fixed parameter FLC and to avoid performance degradation of the machine drive. It can update the FLC parameters in accordance to any variation, changes or disturbances that may occur to the drive system. However, FLC system requires huge computation capacity which increases the computational burden of the overall machine drive system and may result in poor performance. This research proposed a simple ST-FLC mechanism to tune the main FLC speed controller. Three different rule-size of FLC (9, 25, and 49) rules are implemented with ST-FLC mechanism based Induction Motor (IM) drive. Performance comparison of the three different rule-size based ST-FLC is conducted based on simulation and experimental analysis. In addition, a computational effort is technically analyzed and compared for the three different rule-size. In the experiment, ST-FLC with less number of rules (9-rules) shows superior performance, lower sampling and lower computational efforts compared to ST-FLC with higher rule-size (25, 49) rules.